A Novel Approach to Low Temperature Thermal Reverse Osmosis Desalination. (2015) - Nihill, Jack; Leary, Martin; Date, Abhijit
Abstract: This paper presents the initial concept design for a novel high pressure thermal water pump for use in a reverse osmosis desalination system working on a new thermal power cycle referred to as the thermal power pump cycle (TPP). The operation and design of the proposed TPP cycle operated reverse osmosis system are explained with the help of system schematics. Basic governing equations used to carry out the theoretical analysis of the proposed system are discussed. Theoretical performance of the thermal power pump cycle with isopentane as the working fluid is presented. A series of experiments have been carried out to determine the effectiveness of the new power cycle, agreement with theoretical predictions, and the major areas that will require further development.